Nurturing Reading Culture: Establishing a Mini Library to Promote Literacy and Foster Children's Reading Interest in Cidikit Village, Bayah, Lebak, Banten - Anne Gunawati; Muhamad Muslih; Yuniar Calisna (Probono and Community Service Journal, 2022)
. According to the observations made in Cidikit Village's primary and junior high schools, pupils' lack of interest in reading affected their willingness to visit the library. This is because there are few books, the kids from Cidikit Village and the Village Reading Park live quite far apart, and school reading is not a habit. A reading garden was created by Jumyadi, an elementary school teacher in Cidikit Village, out of worry for his kids' ability to learn. It is envisaged that adding micro libraries to each settlement in Cidikit Village will contribute to the children's literacy growth. The PAR (Participatory Action Research) method was used to carry out this research. The social phenomena of Taman Baca are observed, heard, and understood using this technique. Cidikit Village benefits significantly from Al-Fatih Reading Park's existence as a hub for local knowledge.